Barriers to Adherence to Standard of Care in Appalachia: A Qualitative Assessment in Gastrointestinal Cancers - Levy BE; Castle JT; Bardhan R; Dignan M; Bhakta A (Patient Preference and Adherence)
Brittany E Levy,1 Jennifer T Castle,1 Roshmita Bardhan,2 Mark Dignan,3 Avinash Bhakta1 1Division of Colorectal Surgery, University of Kentucky College of Medicine, Lexington, KY, USA; 2Mercy Health – The Jewish Hospital, Cincinnati, OH, USA; 3Department of Internal Medicine, University of Kentucky College of Medicine, Lexington, KY, USACorrespondence: Mark Dignan, Department of Internal Medicine, University of Kentucky College of Medicine, 760 Press Avenue, Room 335, Lexington, KY, 40536-0679, USA, Tel +1 859 913 0207, Email Mark.dignan@uky.eduPurpose: Appalachian Kentucky, a 32-county region in the eastern part of the state, has elevated colon cancer mortality rates. While recommended as the standard of care, access to adjuvant chemotherapy treatment is limited in this region due to scarce health services and significant social and geographical barriers. The purpose of this investigation was to improve understanding of barriers that cancer patients residing in rural areas not served directly by tertiary medical systems must overcome in completing adjuvant therapy.Methods: Participants were recruited from two medical centers: A tertiary care NCI designated Cancer Center and a regional hospital. Participants underwent a 15– 20 minute interview to assess factors associated with adherence to adjuvant treatment recommendations. Grounded theory identified themes related to patient behaviors and non-adherence to standard of care recommendations.Results: Data were collected in 45 telephone and in-person patient interviews, 26 from an NCI-designated cancer center and 19 from a rural hospital. Statistically the two groups were equivalent in terms of age, subjective health status, and medical comorbidities. Six themes were identified from analysis of the transcribed interviews including: confidence in my care provider, communication, treatment issues, distrust, faith, and barriers to obtaining healthcare. Participants completing adjuvant therapy were more likely to express trust in their provider and describe fewer barriers to obtaining healthcare than those not completing adjuvant therapy.Conclusion: Barriers to completing adjuvant therapy may differ between rural and urban healthcare systems which may yield opportunities for targeted interventions to improve rates of completion of colon cancer adjuvant chemotherapy.Keywords: cancer, rural, barriers to care, adjuvant therapy